2018
DOI: 10.1152/ajpgi.00340.2017
|View full text |Cite
|
Sign up to set email alerts
|

Acute small intestinal inflammation results in persistent lymphatic alterations

Abstract: Inflammatory bowel disease (IBD) has a complex pathophysiology with limited treatments. Structural and functional changes in the intestinal lymphatic system have been associated with the disease, with increased risk of IBD occurrence linked to a history of acute intestinal injury. To examine the potential role of the lymphatic system in inflammation recurrence, we evaluated morphological and functional changes in mouse mucosal and mesenteric lymphatic vessels, and within the mesenteric lymph nodes during acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…A disruption of the mesenteric lymphatic system is a well-documented sign of intestinal inflammation in two animal models of human IBD. 51,52 Whether the disruption in effective lymph flow is driven by the translocated bacteria is still to be validated. However, evidence points to it as being a key component.…”
Section: Discussionmentioning
confidence: 99%
“…A disruption of the mesenteric lymphatic system is a well-documented sign of intestinal inflammation in two animal models of human IBD. 51,52 Whether the disruption in effective lymph flow is driven by the translocated bacteria is still to be validated. However, evidence points to it as being a key component.…”
Section: Discussionmentioning
confidence: 99%
“…During the progression of IBD extra-cellular matrix remodeling is common, the role of this remodeling however, is poorly understood and it is thought that extracellular molecules produced during this destructive/reparative stage may in fact perpetuate inflammation (53). We have previously demonstrated that even after the removal of DSS, remodeled lymphatics persist, a phenomenon that is evident with the IBD patient population (3).…”
Section: Discussionmentioning
confidence: 91%
“…The promotion of lymphangiogenesis within the mesentery of DSS treated animals is a well-documented phenomenon (3, 10). Alongside lymphangiogenesis, vessel dilation mediated by iNOS-dependent production of nitric oxide is a common feature associated with inflammation within the tissue surrounding the lymphatics (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether the increased vessel densities resolve or sustain the IBD is still unclear, these new vasculatures are leaky, which can exacerbate the inflammatory condition. Increased vascular permeability is another key feature during inflammation [99,100]. Additionally, stage-dependent changes in the blood flow have been reported in experimental colitis models.…”
Section: Intestinal Vasculature In Diseasesmentioning
confidence: 99%